Societal Dynamics and Fragility : Engaging Societies in Responding to Fragile Situations - Marc, Alexandre; Willman, Alys; Aslam, Ghazia; Rebosio, Michelle; Balasuriya, Kanishka (Washington, DC: World Bank, 2013)
The objective of the study reported in this book was to understand how societal dynamics can be mobilized toward a convergence across groups in society and thus toward greater social cohesion overall. The team began with an extensive consultation phase to identify some key societal dynamics that seemed important in understanding fragility. The German Development Cooperation (GIZ) was a key partner in the study, providing support to the analytical phase in the form of a background paper, and technical advice throughout the preparation of the report. The team continued to consult with these experts throughout the fieldwork and the writing of the book. This book reports a study about societal relationships in fragile situations. Drawing on relevant literature and fieldwork in five countries, it suggests that fragility, violent conflict, and state failure are functions not only of state inability or unwillingness to perform core tasks, but also of dysfunctional relationships in society that do not permit a state to be formed or sustained. The present chapter has introduced the problem of fragility and suggested that seeing fragility as a problem of relationships in society can lead to more effective interventions in fragile situations. Chapter two turns to a key area of societal relations, the state society relationship in fragile situations. Chapter three begins a conversation about social cohesion in fragile situations. It suggests a critical element of social cohesion: a convergence across groups in society. Chapter four discusses how perceptions of injustice across groups can deepen divisions and hinder coexistence and collective action. Many times such perceptions can be even more influential than measurable differences across groups (such as income inequality) in fomenting resentment and division. Chapter five then takes up the issue of interactions between institutions in fragile situations. It is suggested that social cohesion contributes to more constructive interactions among institutions, increasing their capacity to realize development goals. Chapter six shifts the focus to certain relationships in society that are particularly important for social cohesion. Chapter seven describes an overall approach to policy and programming, including how to conduct research and develop knowledge from this perspective. Chapter eight offers specific orientations for adapting existing tools and instruments to address the societal bases of fragility.